The new accounting standard IFRS 9 and its impact on how banks should provision for credit losses - ALBANNA, AMNA AHMAD (2019)
On Jan, 2018 the new accounting standard International Financial Reporting Standard 9 (IFRS 9) was implemented aiming in simplifying calculation of impairment and other financial measurements. The aim of this study is to examine the new accounting standard and its impact on how banks should provision for Expected Credit Losses (ECL) and its effect on other financial assets. The dissertation is based on qualitative approach where set of interviews with finance and corporate teams of banks and other entities have been contacted. Using semi-structured interviews, respondents were asked to answer the study questions and how banks should provision for expected credit losses under new accounting rule IFRS 9. Knowing and observing new accounting rule is very important. Dissertation focuses on how the new accounting rule start approximating losses when loan is made which will help banks to avoid any bad news such as future recessions, political events, and sitting apart reserves to meet unexpected future losses. Moreover, IFRS 9 impacts many capital ratios such as Capital Adequacy Ratio (CAR) and Common Equity Tier 1 (CET 1). The findings and results of the interview questions were that the new standard will impact the provision part of the banks but this impact will not be dramatic. Moreover, the impairment provision level will increase under IFRS9 around 25%. Under the new accounting rule there are requirement for issuing more equity, since more loans are unexpected to get back from the customers in this situation banks may need more capital to cover the expected losses. IFRS9 also can affect deal pricing under the new standard for risky customers may get higher price than normal customers. Banks in the UAE can take many strategies such as strong relationship, Tighter controls on new originations, and Revisions of Policies & Product characteristics in order to lower the expected provision.